2022
DOI: 10.5455/javar.2022.i645
|View full text |Cite
|
Sign up to set email alerts
|

Cassava pulp added to fermented total mixed rations increased tropical sheep’s nutrient utilization, rumen ecology, and microbial protein synthesis

Abstract: Objective: The price of animal production will be affected by the significant increase in feed costs. The objective of this research was to investigate the impact of adding waste cassava pulp to fer¬mented total mixed ration (FTMR) on nutrient utilization, rumen ecology, and microbial protein synthesis in tropical sheep. Materials and Methods: A 3 × 3 replicated Latin square design was used to randomly arrange nine crossbreed lambs (Santa Inês × Dorper) with an initial body weight (BW) of 18.7 ± 1.6 kg (mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…On the other hand, OM and CP of digestibility were increased when yeast-fermented cassava pulp replaced soybean meal in diets (Sommai et al, 2020). Cassava pulp-fermented Total Mixed Rations (TMR) increased the nutrient digestibility in lambs (Khejornsart et al, 2022), while this has been confirmed previously (Morm et al, 2023) and by this current study. In addition, using concentration assists in boosting nutrient digestibility and intake in cattle (Jiang et al, 2022).…”
Section: Introductionsupporting
confidence: 81%
See 4 more Smart Citations
“…On the other hand, OM and CP of digestibility were increased when yeast-fermented cassava pulp replaced soybean meal in diets (Sommai et al, 2020). Cassava pulp-fermented Total Mixed Rations (TMR) increased the nutrient digestibility in lambs (Khejornsart et al, 2022), while this has been confirmed previously (Morm et al, 2023) and by this current study. In addition, using concentration assists in boosting nutrient digestibility and intake in cattle (Jiang et al, 2022).…”
Section: Introductionsupporting
confidence: 81%
“…Prior studies support each other concerning CP in concentrated and fermented cassava pulp (Sommai et al, 2020). Separately, the current study of Rice Straw (RS) containing CP was varied and found it was better than the previous study (Khejornsart et al, 2022;Gunun et al, 2018;Dagaew et al, 2023), but it was similar to (Sommai et al, 2020).…”
Section: Chemical Composition and Feed Ingredientssupporting
confidence: 50%
See 3 more Smart Citations